Is the speech-language pathology profession prepared for an ageing population? An Australian survey. (4th March 2019) - Bennett, Michelle; Cartwright, Jade; Young, Jessica
Abstract: Purpose : This study profiled the demographic characteristics and practice patterns of speech-language pathologists working with older Australians to inform future workforce planning and service development in response to an ageing population and aged care sector reform. Method : Data were collected through snowball distribution of an online survey comprising six sections: demographic details; caseload and service delivery practices, degree of inter-professional practice; engagement with professional development and support; and assessment and management of swallowing, mealtime and communication difficulties. All data were analysed using descriptive statistics and chi-square to determine the independence of key variables. Result : Data from 145 speech-language pathologists highlight the need for increased numbers of clinicians working outside of metropolitan areas and greater workforce diversity, along with increased incentive, supervision and inter-professional support for new graduate and early career clinicians considering working outside of hospital settings. To ensure evidence-based practice, further research into the validity of current assessment and intervention methods used across aged care settings is needed. Conclusion : The findings highlight the need for an extended scope of practice and improved models of support for speech-language pathologists working with older people to better respond to the needs of an ageing population and on-going aged care sector reform.